2005
DOI: 10.1093/her/cyh023
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of the National Healthy School Standard: using national datasets

Abstract: An evaluation of the National Healthy School Standard (NHSS) was undertaken by the authors on behalf of the Department of Health and the Department for Education and Skills. One part of the evaluation involved gaining access to a number of datasets derived from previous research and analysing the health-related outcomes of schools which had attained Level 3 of the NHSS, compared with those of other schools. The sources which provided the most interesting findings were the Health-Related Behaviour Questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 1 publication
1
22
0
Order By: Relevance
“…Of these seven studies, four were rated as moderate and three as weak. Similarly, five policies negatively impacted health equity , and for all except one , similar policies had neutral or even positive impacts on inequities in other studies. Of the five studies that found negative impacts, two were rated as strong, one was moderate and two were weak.…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations
“…Of these seven studies, four were rated as moderate and three as weak. Similarly, five policies negatively impacted health equity , and for all except one , similar policies had neutral or even positive impacts on inequities in other studies. Of the five studies that found negative impacts, two were rated as strong, one was moderate and two were weak.…”
Section: Resultssupporting
confidence: 58%
“…Ten studies evaluated policies that were fully agentic or had agentic components (Tables and ). The UK 5 a day fruit and vegetable social marketing campaign had a positive impact on inequities , whereas school‐based counselling and educational initiatives negatively impacted inequities in some studies but had no impact in others . Counselling and educational interventions in other contexts (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In England, a National Healthy School Standard was first introduced in 1999, with the aim of promoting social inclusion, reducing inequalities and raising educational achievement (Schagen et al . 2005).…”
Section: Introductionmentioning
confidence: 99%